OPTIMIZATION OF DIGITAL MARKETING AND MANAGEMENT FOR ENHANCE SUSTAINABLE DEVELOPMENT CREATIVE ECONOMY IN ECO-FRIENDLY CIPAYUNG GIRANG VILLAGE - Satria, Wahyu Indra; Mekaniawati, Ani; Sutarti, Sutarti; Aulia, Mira Nur; Aprilia, Thania (LPPM Univ. Ibn Khaldun Bogor, 2024)
Micro, small, and medium enterprises (MSMEs) are businesses that classified by their size, typically based on factors such as the number of employees, annual revenue, and total assets. They play a crucial role in the Indonesian economy, contributing to job creation, innovation, and local development. Several mechanisms that can be used to help advance the sustainability of MSMEs are through information systmes technology such as digital marketing and management. One of the MSMEs businesses owners that exist in Indonesia is Metasgoni. Metasgoni was established in 2011, at Cipayung Girang Village, Bogor–Indonesia. Metasgoni faces several challenges, especially in the management aspect, where Metasgoni's bookkeeping services is still done manually and does not yet have a website for digital marketing needs, which is an important area for further development. The Institut Bisnis dan Informatika Kesatuan Comnunity Service activity action is to optimize Metasgoni digital marketing and management so that Metasgoni can improve sustainable development as a whole.